Good Dances Make Good Guests: Dance, Animation and Sovereign Assertion in ‘Amis Country, Taiwan - Hatfield, DJ W. (Anthropologica, 2020)
<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Within the context of official multiculturalism and the promotion of tourism to improve the economic prospects of Taiwanese Indigenous people, ritual dances of ‘Amis/Pangcah people, known as <em style="box-sizing: border-box; color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">malikoda<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">, have become sites of conflict concerning ritual propriety and performance. Although as participatory practices, malikoda can never be performed for an audience, they have served to mediate outside power, including but not limited to ancestral spirits and political figures. However, whether and how those outside ‘Amis communities can malikoda remains subject to debate. Malikoda animates a model of Indigenous sovereignty, which can flexibly incorporate external forces that impinge on ‘Amis communities. Yet, the felicity conditions for malikoda are unstable. To resolve this, ‘Amis people have relied upon a combination of heritage and local discourses that define the dance as an act of hospitality. Both types require the alignment of various actors, media and interpretations at multiple scales, often obviating interpretation. Thus, attention to malikoda highlights how Indigenous people engage with indigeneity as a cultural resource under multiculturalism and raises broader questions about the role of animation in sovereign assertion.